An innovative solar-powered natural gas-based compressed air energy storage system integrated with a liquefied air power cycle - Sadeghi, Shayan; Ghandehariun, Samane; Rezaie, Behnaz; Javani, Nader (WILEY, 2021)
A novel solar-based compressed air energy storage system is developed and analyzed in this paper. The integrated system includes a multi-stage air compression unit, thermal oil loop, multi-stage gas turbine unit, high-temperature molten salt-based solar power tower unit, liquefied air power cycle, thermoelectric generator, and liquefied natural gas (LNG) regasification unit. A eutectic mixture of carbonate salt is used for thermal energy storage in the solar subsystem. Energy, exergy, and economic analyses are performed to evaluate the performance of the proposed system. A parametric study investigates the effects of important parameters on the performance of the integrated system. The proposed system stores 356 MWh of grid electricity during the charging mode. Considering all the available energy sources, the energy output of the integrated system is 797.6 MWh. Energy and exergy efficiencies of the integrated system are 55.3% and 46.4%, respectively. The results show that the highest contributor to the overall exergy destruction rate of the integrated system is the combustion chamber unit. Finally, levelized cost of electricity is evaluated as 12.4/kWh.
Keywords: compressed air energy storage; economic analysis; energy and exergy analyses; LNG regasification; solar energy; thermal energy storage; EXERGY ANALYSIS; THERMODYNAMIC ANALYSIS; CAES SYSTEM; OPTIMIZATION; TURBINE; WIND; PLANT; COLLECTOR; DESIGN; Energy & Fuels; Nuclear Science & Technology